Meningococcal disease in Italy: public concern, media coverage and policy change - Loredana Covolo; Elia Croce; Marco Moneda; Elena Zanardini; Umberto Gelatti; Peter J. Schulz; Elisabetta Ceretti (BMC, 2019)
Abstract Background Between 2015 and 2017 six deaths due to meningitis in the Lombardy Region, Northern Italy, caught the attention of media and increased concern among the population, with a consequent increase in demand for vaccination. Considering the evidence about the impact of media coverage of health issues on public behaviour, this paper investigates the trend of media coverage and internet searches regarding meningitis in the Lombardy Region. Methods Content analysis of online articles published from January 2015 to May 2017 and analysis of Google Trends were carried out. A codebook was created in order to assess the content of each article analysed, based on six areas: article characteristics, information about meningococcal disease and vaccination, Local Health Authority activities, accuracy of information and tone of the message. Results Both public interest and media attention peaked in December 2016 and January 2017, when the Lombardy Regional Authority changed its policy by offering co-payment to adults with a saving of 50%. The frequency of meningitis coverage decreased after the announcement of policy change. For example, articles containing new information on meningitis or meningococcal vaccine (76 to 48%, p = 0.01) and preventive recommendations (31% down to 10%, p = 0.006) decreased significantly. An alarmist tone appeared in 21% of pre-policy articles that decreased to 5% post-policy (p = 0.03). Conclusions The findings suggest a role for the media in fostering public pressure towards health services and policy-makers. A collaboration between Public Health institutions and the media would be beneficial in order to improve communication with the public.